Analisis Komposisi Hasil Tangkapan Ikan dengan Gill Net atau Jaring Ingsang Hanyut Pelabuhan Perikanan Muara Angke - Taufik Muhammad; Achmad Kusyairi; Alif Astagia (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2025)
This research aims to determine and inform the composition of the results catch (type and quantity) from gillnet fishing gear found in Muara Angke Fishing Harbor. The research was carried out for 3 (two) months starting from October to December at the Muara Angke Fishing Harbor. Data collection was carried out using survey methods and interviews and literature studies. Sampling was carried out using a purposive method sampling based on the function and benefits of the gillnet fishing unit. The number of respondents used in this research was 25 Gill Net vessels in the period October to December 2024 at the Muara Angke Fishing Port. Analysis of the type and number of catches was carried out descriptively. Research result shows that the composition of fish caught using Gill Nets in Muara Angke Fishing Harbor has 19 species of fish caught, with the most commonly caught fish being Gray Tuna with 329,710 kg and the least being Hammerhead Shark with 6 kg.